1973
DOI: 10.1007/bf01868066
|View full text |Cite
|
Sign up to set email alerts
|

Iodination (125I) of the apical plasma membrane of toad bladder epithelium: Electron-microscopic autoradiography and physiological effects

Abstract: Summary. The apical plasma membrane of toad bladder epithelial cells has been enzymatically iodinated, using lactoperoxidase, H20 z (generated by a glucose-glucose oxidase system) and NaI. The site of labeling was demonstrated by electron-microscopic autoradiography; the silver grains (lzsI) were found exclusively overlying the luminal plasma membranes of the epithelium. The iodination reaction reached completion in less than 5 min. The dependence of the degree of iodination on NaI concentrations (range = 6.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Previous studies (29,32) (29,33), and the iodinations were performed at 2TC instead of 23TC. We measured the transepithelial potential difference and ADHinduced water flow in paired hemibladders and observed no difference between untreated hemibladders and those subjected to either of our iodination protocols (data not shown).…”
Section: Lactoperoxidase/glucose Oxidase Iodination Of the Apicalmentioning
confidence: 99%
“…Previous studies (29,32) (29,33), and the iodinations were performed at 2TC instead of 23TC. We measured the transepithelial potential difference and ADHinduced water flow in paired hemibladders and observed no difference between untreated hemibladders and those subjected to either of our iodination protocols (data not shown).…”
Section: Lactoperoxidase/glucose Oxidase Iodination Of the Apicalmentioning
confidence: 99%
“…The fixed particulates were collected by centrifugation at 100,000 • g for 1 hr. The pellets were washed three times with 0.4 ml, 200 mM sodium cacodylate, pH 7.5, post-fixed in 2% osmium tetroxide in 100 mM sodium cacodylate, pH 7.5 an d processed for electron microscopy as previously described [31].…”
Section: Morphologymentioning
confidence: 99%
“…The validity of enzymatic markers relies on the results of histochemical analysis, which assigns a given enzymatic activity to a particular organelle or recognizable membrane element [6,7]. The limitations inherent in histochemical analysis prompted attempts to develop alternative approaches, including the use of surface antigens, membrane receptors (lectins, hormones, cholera toxin), or covalently attached radioactive labels [3,5,24,31]. We elected to explore the utility of covalent, radioactive membrane markers in analysis of the biochemical properties of epithelial plasma membranes of the urinary bladder of the toad [26].…”
mentioning
confidence: 99%
“…After dehydration in a graded series of aqueous ethanol solutions, the tissues were embedded in Epon 812 [19]. Light and electron-microscopic autoradiographs were obtained as described previously [26].…”
Section: Light and Electron-microscopic Autoradiographymentioning
confidence: 99%
“…In an earlier study, Strum and Edelman [26] reported covalent labeling of the apical plasma membrane of toad bladder with 12sI activated by the glucose oxidase-lactoperoxidase system. The availability of multiple iodine isotopes and the prospect of group specific labeling in the same membrane (i.e., the apical leaflet), with two different reagents prompted us to explore the potential utility of 125I-DDISA.…”
mentioning
confidence: 98%